2020
DOI: 10.7759/cureus.11331
|View full text |Cite
|
Sign up to set email alerts
|

Gall Bladder Wall Thickening in Dengue Fever – Aid in Labelling Dengue Hemorrhagic Fever and a Marker of Severity

Abstract: Introduction Dengue fever is a mosquito-borne viral disease spread by the bite of the Aedes aegypti mosquito. Dengue epidemics have contributed to a great economic burden, especially in SouthEast Asia. This study aimed to determine gall bladder wall thickness (GBWT) in patients with dengue fever, assess its sensitivity and specificity to identify dengue hemorrhagic fever, and also compare gall bladder wall thickening (GWBT) with platelets, hematocrit, and leucocyte count. Materials and methods This prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Forty-three studies met the inclusion criteria [ 8 50 ] which included 40 hospital based and 3 community based cohorts that collectively recruited 15,794 patients (Table 1 ). Another ten studies [ 51 60 ] initially considered as eligible, were later excluded due to a high probability of reporting on same cohorts in the included studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-three studies met the inclusion criteria [ 8 50 ] which included 40 hospital based and 3 community based cohorts that collectively recruited 15,794 patients (Table 1 ). Another ten studies [ 51 60 ] initially considered as eligible, were later excluded due to a high probability of reporting on same cohorts in the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies reported the proportion of patients with plasma leakage out of all symptomatic and hospitalised patients (Table 2 ), but the method of diagnosis was inconsistent. Six studies predominantly relied on ultrasonography [ 8 , 20 , 32 , 36 , 41 , 42 ] while the remainder used chest X-ray alone, [ 12 ] chest X-ray with ultrasonography, [ 35 ] ultrasonography and a rise in haematocrit > 20%, [ 43 , 49 ] a rise in haematocrit (> 20% or > 15%) with clinical examination [ 18 , 45 , 50 ] or clinical examination alone [ 26 ]. One study did not mention the method of diagnosis [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thrombocytopenia is a classical of dengue infection, and this can be caused due to binding of platelets to the activated endothelial cells (Teixeira et al 2008). It was reported that the edema of the gall bladder is associated with the dengue hemorrhagic fever, so every dengue patient should be screened for it (Adil et al 2020). The sensitivity and specificity of the thickness of the gall bladder in assessing the admission to the intensive care unit or general ward were 100% and 62.1% (Ibrahim et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The same radiologist performed all the ultrasound abdomen examinations, to avoid the inter observer bias. The serum ferritin level is considered as high if it is more than 500 ng/ml (Senjo et al 2018) and more than 3 mm of gall bladder wall thickness was considered as the significant edema (Adil et al 2020). This study did not include the controls as the serum ferritin levels, and ultrasound abdomen were not done in other cases of fever, which were negative for the NS1 antigen card test.…”
Section: Methodsmentioning
confidence: 99%